Hepatic encephalopathy in acute liver failure: a primary neurogliopathy - Butterworth, Roger F. (Henry Stewart Talks, 2013)
Classification of hepatic encephalopathy, Acute liver failure, Neuropathology of Acute liver failure, Pathogenesis of hepatic encephalopathy in Acute liver failure: key role of ammonia, Arterial NH3: risk factor of intracranial hypertension, Selective gene expression alterations in Acute liver failure, Glial fibrillary acidic protein (GFAP), Glutamate transporter EAAT-2, Extracellular brain glutamate and neurological status, Systemic inflammation in Acute liver failure, Brain cytokines in Acute liver failure, Therapeutic implications